Improve the mathematical literacy ability of junior high school students through a contextual approach - Nuurjannah, Putri Eka Indah; Sayoga, Repanda (IKIP Siliwangi, 2020)
The aim of this study was to examine the achievement and improvement of MLA of junior high school students who obtained a CA and obtained CL. The method used is quasi-experiment design with a nonequivalent control group. This research was conducted in SMPN in West Bandung Regency with a sample of grade 8th students as many as 33 experiment class students and 27 control class students. The instrument used was the MLA 3rd level test as many as 2 items and 4th level as many as 3 items. The data analysis used was the Mann-Whitney U test. The results of the study found that 1) MLA's initial in both classes was the same; 2) the average posttest that gets contextual learning and those who get regular learning is quite different; 3) Mann Whitney U test scores on the posttest and normalized gain obtained Sig. = 0,000 < 0,05, then Ho is rejected. This means that the achievement of MLA of students who get CA is better than those who get CL. The same gain also in the normalized gain, Sig. < 0.05, meaning that the increase in MLA of students who get CA is better than those who get CL.